A silicon-carbon composite material and a method for preparing a silicon-carbon composite material using photovoltaic silicon powder and applications thereof
Patent Information
- Application Number
- CN202611296957.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
(1)性能不足:首次库伦效率低(≤80%)、可逆容量低(≤280mAh/g)、循环稳定性差;
本发明方法制得的硬碳负极材料在关键指标上均表现优异—首次库伦效率(≥86.5%)、0.1C可逆容量(≥292 mAh/g)、循环寿命(1C循环200周保持率≥82%),综合性能优于商用椰壳硬碳。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of high-value utilization of photovoltaic solid waste and preparation of sodium-ion battery materials, specifically to a method for preparing silicon-carbon composite materials using photovoltaic silicon powder and its application. Background Technology
[0002] With the rapid development of the global photovoltaic industry, my country's retired photovoltaic modules will exceed 5 million tons by 2030. During the pyrolysis and crushing process, approximately 5% to 8% silicon powder (mainly elemental silicon, with a content ≥98%) will be generated. Currently, this silicon powder is only used as a low-end industrial filler, resulting in a serious waste of silicon resources. Meanwhile, for sodium-ion batteries, a core technology in large-scale energy storage, hard carbon anode materials are a key bottleneck for their industrialization. Traditional hard carbon anodes mainly use biomass such as coconut shells and bamboo charcoal as raw materials, and have the following core defects: (1) Inadequate performance: low initial coulombic efficiency (≤80%), low reversible capacity (≤280mAh / g), and poor cycle stability; (2) High cost: Biomass raw materials are expensive and the supply is unstable, resulting in high production costs; (3) High environmental pressure: The carbonization process of biomass produces a large amount of tar and waste gas, which is difficult to treat.
[0003] In particular, sodium-ion batteries and lithium-ion batteries have fundamentally different energy storage mechanisms: the radius of sodium ions (1.02 Å) is much larger than that of lithium ions (0.76 Å), and traditional graphite anodes have almost no sodium storage capacity due to their small interlayer spacing (0.335 nm). Therefore, sodium-ion battery anodes must use hard carbon materials with disordered carbon layer structure, large interlayer spacing (>0.37 nm), and abundant nanopores, rather than the graphite or silicon-carbon composite materials commonly used in lithium batteries.
[0004] In existing technologies, there are reports on the preparation of silicon-carbon composite materials from waste photovoltaic silicon powder for lithium-ion batteries (such as CN117263189A, CN117712321A, CN116253325A, etc.). However, these technologies are all aimed at lithium-ion battery anodes, preparing silicon-carbon composite materials rather than hard carbon materials, and do not involve activation and pore-forming steps. Moreover, the coating method is mostly dry mixing, which is fundamentally different from the technical route and application direction of this invention. Currently, there are no reports on preparing sodium-ion battery hard carbon anodes from retired photovoltaic silicon powder through a "carbonization-activation-coating" process. Summary of the Invention
[0005] To address the aforementioned problems, this invention employs an integrated process of "silicon powder gradient purification → ball milling interface composite → water vapor gradient activation pore formation → asphalt liquid phase coating" to convert retired photovoltaic silicon powder into high-performance hard carbon anode material for sodium-ion batteries.
[0006] To achieve the objectives of this invention, the following technical solution is adopted: In a first aspect, this invention provides a method for preparing silicon-carbon composite materials using photovoltaic silicon powder, comprising the following steps: S1. Pretreatment: High-purity photovoltaic silicon powder is obtained by classifying, magnetically separating and removing impurities from pyrolytic silicon powder of retired photovoltaic modules or crushed silicon wafers and then acid washing. S2. Ball milling: The high-purity photovoltaic silicon powder and flake graphite powder obtained in S1 are mixed with phenolic resin and then ball milled to obtain silicon powder-graphite composite powder. S3. Carbonization and activation: Under an inert atmosphere, the silicon powder-graphite composite powder obtained in S2 is fed into a tube furnace for carbonization reaction. After cooling, water vapor is introduced into the furnace for activation to obtain porous silicon-carbon composite hard carbon. S4. Liquid phase coating and classification: The porous silicon-carbon composite hard carbon is placed in an asphalt coating liquid, the solid is filtered out and dried, and a composite hard carbon material with a carbon coating layer is formed at 800~900℃. After crushing and classification, a silicon-carbon composite material is obtained.
[0007] In some embodiments, in S1, the acid washing process is as follows: the silicon powder after magnetic separation and impurity removal is placed in a mixed acid solution of dilute hydrochloric acid and hydrofluoric acid and stirred, filtered and washed with water until neutral, and then vacuum dried. Preferably, the solid-liquid ratio of the silicon powder to the mixed acid solution is 1:(10~15); the mixed acid solution is obtained by mixing 1~2 mol / L dilute hydrochloric acid solution with 0.2~0.5 mol / L hydrofluoric acid. More preferably, vacuum drying is performed at 120~150℃ for 12~24 h.
[0008] In some embodiments, in S2, based on the total mass of high-purity photovoltaic silicon powder and flake graphite powder being 100%, the amount of phenolic resin added is 3% to 5%; Preferably, the mass ratio of the high-purity photovoltaic silicon powder to the flake graphite powder is 1:(5~10); More preferably, the ball milling is carried out at a rotation speed of 300~500 r / min for 2~4 h; More preferably, the ball-to-material ratio of the ball mill is (10~15):1, and the filling rate of the grinding beads is 70%~80%.
[0009] In some embodiments, in step S3, the temperature is increased to 1000-1200°C at a rate of 5-10°C / min, and the carbonization reaction is carried out after holding at that temperature for 2-4 hours.
[0010] In some embodiments, after the carbonization reaction is completed, the temperature of the system is lowered to 800-900°C and then activated by introducing steam. Preferably, the activation is carried out for 30 to 60 minutes under a water vapor flow rate of 50 to 100 sccm.
[0011] In some embodiments, in S4, porous silicon-carbon composite hard carbon and asphalt coating liquid are mixed at a solid-liquid ratio of 1: (5~15), and then stirred at a speed of 300~600 r / min for 30~60 min. Preferably, the asphalt coating liquid is a mixture of asphalt and ethanol, wherein the concentration of asphalt is 5% to 10%; More preferably, the asphalt is selected from petroleum asphalt or coal tar pitch, with a softening point of 120~150℃.
[0012] In some implementations, the temperature is increased to 800-900°C at a rate of 1-5°C / min under argon protection and held for 1-2 hours.
[0013] In some embodiments, an air jet mill is used to pulverize the material at a pressure of 0.6 to 1.0 MPa, and after air jet classification, a silicon-carbon composite material with a particle size of 5 to 20 μm and a particle size distribution index ≤ 0.2 is obtained. Preferably, the airflow classification is performed using a combination of a two-stage cyclone separator and a bag filter.
[0014] In a second aspect, the present invention provides a silicon-carbon composite material prepared by the above method.
[0015] In a third aspect, the present invention provides a sodium-ion battery comprising the above-mentioned silicon-carbon composite material, characterized in that the initial charge-discharge efficiency of the sodium-ion battery is ≥86%.
[0016] The technical solution provided by this invention has the following beneficial effects: The hard carbon anode material prepared by the method of this invention exhibits excellent performance in key indicators—first coulombic efficiency (≥86.5%), 0.1C reversible capacity (≥292 mAh / g), and cycle life (retention rate ≥82% after 200 cycles at 1C), with overall performance superior to commercial coconut shell hard carbon.
[0017] The preparation method provided by this invention transforms low-value photovoltaic solid waste silicon powder into high-performance sodium-ion battery hard carbon anode material, significantly reducing the overall production cost compared to commercial coconut shell hard carbon. At the same time, the entire preparation process is free of toxic reagents, the acid washing wastewater reuse rate is ≥93%, and the carbonization tail gas is treated to meet emission standards, perfectly responding to the "dual carbon" strategy and the requirements of zero-waste city construction. Attached Figure Description
[0018] Figure 1 XRD pattern of the S3 carbonization reaction product in Example 1 of this invention; Figure 2SEM image of the S3 water vapor activation product in Example 1 of this invention; Figure 3 : Figure 2 A magnified view of a portion of the image. Detailed Implementation
[0019] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The term "and / or" may be used herein to include any and all combinations of one or more of the associated listed items.
[0021] This invention provides a method for preparing silicon-carbon composite materials using photovoltaic silicon powder, comprising the following steps: S1. Pretreatment: Collect pyrolytic silicon powder from retired photovoltaic modules or crushed silicon wafers, and sequentially process them through diversion and classification (the particle size obtained from classification is 1~5 μm), magnetic separation to remove impurities, and acid washing to obtain high-purity photovoltaic silicon powder (purity ≥99.9%, total metal impurity content ≤50 ppm, particle size 1~5 μm). S2. Ball milling: The high-purity photovoltaic silicon powder and flake graphite powder obtained in S1 are mixed with phenolic resin and then ball milled to obtain silicon powder-graphite composite powder. S3. Carbonization and activation: Under an inert atmosphere, the silicon powder-graphite composite powder obtained in S2 is fed into a tube furnace for carbonization reaction. After cooling, water vapor is introduced into the furnace for activation to obtain porous silicon-carbon composite hard carbon. S4. Liquid phase coating and classification: The porous silicon-carbon composite hard carbon is placed in an asphalt coating liquid, the solid is filtered out and dried, and a composite hard carbon material with a carbon coating layer is formed at 800~900℃. After crushing and classification, a silicon-carbon composite material is obtained.
[0022] In a specific embodiment of the preparation method S1 of the present invention, the acid washing process can be carried out according to the following process: prepare a mixed acid solution of dilute hydrochloric acid and hydrofluoric acid, place the silicon powder after magnetic separation and impurity removal into the above mixed acid solution and stir, then filter, wash with water until neutral, and then vacuum dry. In some specific embodiments, the solid-liquid ratio of the pyrolytic silicon powder or crushed silicon wafer powder to the mixed acid solution is 1:(10~15); the mixed acid solution is obtained by mixing 1~2 mol / L dilute hydrochloric acid solution with 0.2~0.5 mol / L hydrofluoric acid; in some embodiments, the pickling wastewater is recycled after being neutralized with lime and finely filtered, with a recycling rate of ≥93%.
[0023] In some specific implementations, vacuum drying is performed at 120~150℃ (e.g., 125℃, 130℃, 140℃) for 12~24 h, e.g., 15 h, 18 h, 20 h, 22 h.
[0024] In a specific embodiment of the preparation method S2 of the present invention, a phenolic resin binder is added to a mixture of high-purity photovoltaic silicon powder and flake graphite powder, and then the mixture is fed into a planetary ball mill for ball milling. The amount of phenolic resin added is 3% to 5% of the total mass of the high-purity photovoltaic silicon powder and flake graphite powder, for example, 4% or 4.5%. In a preferred embodiment, the ball milling is performed at a speed of 300 to 500 r / min for 2 to 4 hours to obtain a silicon powder-graphite composite powder with uniform silicon powder dispersion. More preferably, the ball-to-material ratio in this ball milling step can be controlled at (10 to 15):1, for example, 12:1, 13:1, or 14:1. Specifically, φ3 to φ10 mm zirconia grinding beads can be used, with a filling rate of 70% to 80%, for example, 75%.
[0025] The flake graphite powder used in this invention has a relatively regular two-dimensional layered crystal structure and oriented arrangement, while ordinary graphite powder (such as earthy graphite or spherical graphite) has a disordered crystal structure and irregular morphology. The ordered layered structure allows silicon powder to be uniformly embedded between layers during ball milling, and after carbonization and activation, it forms an ordered hard carbon skeleton with a large interlayer spacing, thereby significantly improving the initial coulombic efficiency and cycle stability of sodium-ion batteries.
[0026] In a specific embodiment of preparation method S3 of the present invention, the silicon powder-graphite composite powder obtained in S2 is fed into a tube furnace and heated to 1000-1200°C, for example, 1100°C, or 1150°C, at a rate of 5-10°C / min (e.g., 6°C / min, 8°C / min) under an inert atmosphere (flow rate of 200-300 sccm). After holding at this temperature for 2-4 h, a carbonization reaction is carried out, transforming the phenolic resin into a hard carbon framework with a disordered layered structure. The temperature is then lowered to 800-900°C, and water vapor (flow rate of 50-100 sccm) is introduced for activation for 30-60 min, for example, 40 min, or 50 min, constructing a hierarchical pore structure dominated by mesopores within the hard carbon framework, thus obtaining porous silicon-carbon composite hard carbon. Specifically, the specific surface area of the activated material is 120-180 nm. m² / g, pore size distribution is mainly mesopores of 2~5nm, mesopores account for ≥60%, and porosity is 32%~38%.
[0027] In a specific embodiment of the preparation method S4 of the present invention, porous silicon-carbon composite hard carbon and asphalt coating liquid are mixed in a solid-liquid ratio of 1: (5~15), and then stirred at a speed of 300~600 r / min for 30~60 min, so that the asphalt is fully dissolved in the liquid phase and uniformly penetrates into the mesopores of the hard carbon.
[0028] In some preferred embodiments, the asphalt coating liquid is a mixture of asphalt and ethanol, wherein the concentration of asphalt is 5% to 10%; more preferably, the asphalt is selected from petroleum asphalt or coal tar pitch, and the softening point is 120 to 150°C, for example, 130°C or 140°C.
[0029] In some preferred embodiments, the separated solid is dried and then heated to 800-900°C at a rate of 1-5°C / min under argon protection, and held at that temperature for 1-2 h to form a continuous and uniform carbon coating layer with a thickness of 50-200 nm.
[0030] In some specific implementations, an air jet mill is used to pulverize the silicon-carbon composite material under a pressure of 0.6~1.0 MPa, and the material is then classified by air jet to obtain a silicon-carbon composite material with a particle size of 5~20 μm and a particle size distribution index (PDI) ≤0.2. The air jet classification is carried out by a combination of a two-stage cyclone separator and a bag filter.
[0031] The present invention also provides a silicon-carbon composite material prepared by the above method.
[0032] The present invention also provides a sodium-ion battery comprising the above-mentioned silicon-carbon composite material, wherein the initial coulombic efficiency of the sodium-ion battery is ≥86%.
[0033] The present invention will be further illustrated below with specific examples, but it should not be construed as the present invention being limited to these examples.
[0034] Where specific experimental steps or conditions are not specified in the examples, they can be performed according to the corresponding conventional experimental steps or conditions in this technical field. Reagents whose manufacturers are not specified are all conventional reagents already available in this field.
[0035] The source information of the raw materials used in the following examples is as follows: 1. Pyrolytic silicon powder from retired photovoltaic modules: sourced from Guoneng Longyuan Environmental Protection's Qufu recycling production line; composition: Si 98.5%, Fe 42 ppm, Al 28 ppm, Cu 15 ppm, other 15 ppm; 2. Flake graphite powder: Qingdao Guangxing Electronic Materials Co., Ltd., high-purity flake graphite series; purity 99.9%, particle size 10 μm; 3. Phenolic resin: Jiangsu Wuxi Xinming Chemical Co., Ltd., type 2123 thermoplastic phenolic resin; 4. Petroleum asphalt; Hebei Yixiang New Material Technology Co., Ltd., high-temperature petroleum asphalt, softening point 135℃.
[0036] The test data in this invention example are obtained using the following method: 1. XRD crystal phase analysis: GB / T 30904-2014 "X-ray diffraction method for crystal structure analysis of inorganic chemical products"; 2. SEM: JY / T 0584-2020 "General Rules for Analytical Methods of Scanning Electron Microscopy"; 3. Volume expansion rate test: In-situ XRD combined with scanning electron microscopy was used to test the thickness change of the electrode after 200 cycles and calculate the volume expansion rate.
[0037] Example 1 S1. Pretreatment: 100 kg of pyrolytic silicon powder from retired photovoltaic modules was subjected to air classification to obtain 1-5 μm particles. After iron removal by magnetic separation at 15000 Gs, the iron-removed silicon powder was placed in a mixed acid solution (1 mol / L hydrochloric acid + 0.2 mol / L hydrofluoric acid) at a solid-liquid ratio of 1:10 for acid washing. After stirring at 60℃ for 2 h, the powder was filtered and washed with water until pH=7. Then, it was vacuum dried at 120℃ for 12 h to obtain 92.5 kg of high-purity silicon powder with a purity of 99.92% and a total metal impurity content of 42 ppm. S2. Ball milling: 92.5 kg of high-purity photovoltaic silicon powder obtained in S1 was mixed with 740 kg of flake graphite powder (mass ratio 1:8), and 33.3 kg of phenolic resin was added before feeding it into a planetary ball mill. 9990 kg of φ5mm zirconia beads (ball-to-material ratio 12:1) were added, with a filling rate of 75%. The ball mill was set to a speed of 400 r / min and ball milled for 3 hours to obtain silicon powder-graphite composite powder. S3. Carbonization and activation: The silicon powder-graphite composite powder is fed into a tube furnace and heated to 1100℃ at a rate of 8℃ / min under an argon atmosphere (flow rate 250 sccm). The carbonization reaction is carried out after holding at this temperature for 3 hours, so that the phenolic resin is transformed into a disordered hard carbon skeleton. Then, after cooling to 850℃, water vapor (80 sccm) was introduced into it for activation for 45 min, and then it was naturally cooled to room temperature to obtain porous silicon-carbon composite hard carbon. S4. Liquid phase coating and classification: The activated porous silicon-carbon composite hard carbon was added to an ethanol solution of asphalt (concentration of 8%) at a solid-liquid ratio of 1:5. The mixture was stirred at 300 r / min for 30 min. After filtering to separate the solid, it was dried and heated to 850℃ at 5℃ / min under argon protection and held for 1.5 h to form a composite hard carbon material with a carbon coating layer. After being pulverized by air jet milling (0.8 MPa) and classified, silicon-carbon composite materials with a particle size of 5~20 μm and PDI=0.15 were obtained.
[0038] From the instruction manual Figure 1 It can be seen that 2θ has a broad, rounded peak between 22° and 25°, and no sharp crystal characteristic diffraction peaks were observed. This indicates that the material obtained by carbonization reaction in step (3) does not have long-range three-dimensional crystalline order and presents a disordered layer structure, with only local short-range layered order.
[0039] From the instruction manual Figure 2-3 It can be seen that the surface of the material after activation by water vapor in step (3) is porous and not continuous or dense.
[0040] Example 2 Silicon-carbon composite materials were prepared according to the method of Example 1, except that the mixing ratio of high-purity photovoltaic silicon powder and flake graphite powder in S2 was 1:5.
[0041] Example 3 Silicon-carbon composite materials were prepared according to the method of Example 1, except that the mixing ratio of high-purity photovoltaic silicon powder and flake graphite powder in S2 was 1:10.
[0042] Example 4 Silicon-carbon composite materials were prepared according to the method in Example 1, except that in S3, the temperature was increased to 1000°C at a rate of 8°C / min and the carbonization reaction was carried out at the temperature for 3 hours.
[0043] Example 5 Silicon-carbon composite materials were prepared according to the method in Example 1, except that in S3, the temperature was increased to 1200°C at a rate of 8°C / min and held at that temperature for 3 hours for carbonization reaction.
[0044] Example 6 The silicon-carbon composite material was prepared according to the method of Example 1, except that water vapor (80 sccm) was introduced into S3 for activation for 30 min.
[0045] Example 7 The silicon-carbon composite material was prepared according to the method of Example 1, except that water vapor (80 sccm) was introduced in S3 for activation for 60 min.
[0046] Example 8 Silicon-carbon composite materials were prepared according to the method in Example 1, except that S1 used decommissioned silicon wafer fragments as silicon raw material.
[0047] Example 9 A continuous production test of 200 kg / h was conducted with the process parameters of Example 1, and the test was carried out continuously for 168 hours.
[0048] Comparative Example 1 Silicon-carbon composite materials were prepared according to the method in Example 1, except that S2 only added silicon powder directly and did not add flake graphite powder.
[0049] Comparative Example 2 Silicon-carbon composite materials were prepared according to the method of Example 1, except that no phenolic resin binder was added in S2.
[0050] Comparative Example 3 Silicon-carbon composite materials were prepared according to the method in Example 1, except that the water vapor activation process was omitted in S3.
[0051] Comparative Example 4 The silicon-carbon composite material was prepared according to the method of Example 1, except that the surface coating process in S4 was not performed.
[0052] Comparative Example 5 The silicon-carbon composite material was prepared according to the method of Example 1, except that S4 was carried out in the following manner: 8% asphalt powder was added to the porous silicon-carbon composite hard carbon obtained in S3 and dry-mixed, then carbonized at 850°C, and obtained after crushing and grading.
[0053] The silicon-carbon composite material, conductive agent (Super P), and binder (CMC / SBR) prepared above were mixed at a mass ratio of 8:1:1, coated onto copper foil, vacuum dried at 120℃ for 12h, pressed into sheets, and cut into φ14mm electrodes. Using metallic sodium as the counter electrode and 1mol / L NaClO4 / EC+DMC+EMC (1:1:1) as the electrolyte, CR2032 button batteries were assembled. The charge-discharge performance (voltage range 0.01~2.5V) was tested on the Blue Electric test system, and the AC impedance was tested on the electrochemical workstation. The measured electrical performance data are shown in Table 1 below.
[0054] Table 1
[0055] The method for preparing silicon-carbon composite materials using photovoltaic silicon powder provided by this invention solves the industry pain points of low-value utilization of retired photovoltaic silicon powder and poor performance and high cost of traditional hard carbon anodes.
[0056] This invention employs a gentle acid washing method for pyrolytic silicon powder / crushed silicon wafers, eliminating the need for high-temperature calcination. This method is simple, environmentally friendly, and produces hard carbon anode materials with superior overall performance compared to commercially available coconut shell hard carbon, making it a viable alternative to traditional biomass hard carbon for sodium-ion batteries.
[0057] The preparation method of this invention realizes the cross-border integration of photovoltaic solid waste and sodium-ion battery industry, and has broad market application prospects.
Claims
1. A method for preparing silicon-carbon composite materials using photovoltaic silicon powder, characterized in that, Includes the following steps: S1. Pretreatment: High-purity photovoltaic silicon powder is obtained by classifying, magnetically separating and removing impurities from pyrolytic silicon powder of retired photovoltaic modules or crushed silicon wafers and then acid washing. S2. Ball milling: The high-purity photovoltaic silicon powder and flake graphite powder obtained in S1 are mixed with phenolic resin and then ball milled to obtain silicon powder-graphite composite powder. S3. Carbonization and activation: Under an inert atmosphere, the silicon powder-graphite composite powder obtained in S2 is fed into a tube furnace for carbonization reaction. After cooling, water vapor is introduced into the furnace for activation to obtain porous silicon-carbon composite hard carbon. S4. Liquid phase coating and classification: The porous silicon-carbon composite hard carbon is placed in an asphalt coating liquid, the solid is filtered out and dried, and a composite hard carbon material with a carbon coating layer is formed at 800~900℃. After crushing and classification, a silicon-carbon composite material is obtained.
2. The method according to claim 1, characterized in that, In S1, the acid washing process is as follows: the silicon powder after magnetic separation and impurity removal is placed in a mixed acid solution of dilute hydrochloric acid and hydrofluoric acid and stirred, filtered and washed with water until neutral, and then vacuum dried. Preferably, the solid-liquid ratio of the silicon powder to the mixed acid solution is 1:(10~15); the mixed acid solution is obtained by mixing 1~2 mol / L dilute hydrochloric acid solution with 0.2~0.5 mol / L hydrofluoric acid. More preferably, vacuum drying is performed at 120~150℃ for 12~24 h.
3. The method according to claim 1 or 2, characterized in that, In S2, based on the total mass of high-purity photovoltaic silicon powder and flake graphite powder being 100%, the amount of phenolic resin added is 3%~5%; Preferably, the mass ratio of the high-purity photovoltaic silicon powder to the flake graphite powder is 1:(5~10); More preferably, the ball milling is carried out at a rotation speed of 300~500 r / min for 2~4 h; More preferably, the ball-to-material ratio of the ball mill is (10~15):1, and the filling rate of the grinding beads is 70%~80%.
4. The method according to claim 3, characterized in that, In S3, the temperature is increased to 1000-1200℃ at a rate of 5-10℃ / min, and the temperature is held for 2-4 h before the carbonization reaction is carried out.
5. The method according to claim 4, characterized in that, After the carbonization reaction is completed, the temperature of the system is lowered to 800-900℃ and then water vapor is introduced for activation. Preferably, the activation is carried out for 30 to 60 minutes under a water vapor flow rate of 50 to 100 sccm.
6. The method according to any one of claims 1 to 5, characterized in that, In S4, porous silicon-carbon composite hard carbon and asphalt coating liquid are mixed at a solid-liquid ratio of 1: (5~15), and then stirred at a speed of 300~600 r / min for 30~60 min. Preferably, the asphalt coating liquid is a mixture of asphalt and ethanol, wherein the concentration of asphalt is 5% to 10%; More preferably, the asphalt is selected from petroleum asphalt or coal tar pitch, with a softening point of 120~150℃.
7. The method according to claim 6, characterized in that, Under argon protection, the temperature is increased to 800-900℃ at a rate of 1-5℃ / min and held for 1-2 hours.
8. The method according to claim 7, characterized in that, A silicon-carbon composite material with a particle size of 5-20 μm and a particle size distribution index ≤0.2 was obtained by pulverizing the material using an air jet mill at a pressure of 0.6-1.0 MPa and then classifying it by air jet. Preferably, the airflow classification is performed using a combination of a two-stage cyclone separator and a bag filter.
9. A silicon-carbon composite material prepared by any one of claims 1 to 8.
10. A sodium-ion battery comprising the silicon-carbon composite material of claim 9, characterized in that, The initial charge-discharge efficiency of the sodium-ion battery is ≥86%.
Citation Information
Patent Citations
Recycling method of silicon in scrapped photovoltaic cell
CN116253325A
Method for preparing silicon-carbon composite material by utilizing photovoltaic cut square wet silicon powder
CN117263189A
Lithium ion battery negative electrode silicon carbon material, preparation method thereof and lithium ion battery
CN117712321A